A merged magnetotransistor for 3-axis magnetic field measurement based on carrier recombination-deflection effect - Leepattarapongpan, Chana; Phetchakul, Toempong; Penpondee, Naritchaphan; Pengpad, Puttapon; Srihapat, Arckom; Jeamsaksiri, Wutthinan; Chaowicharat, Ekalak; Hruanun, Charndet; Poyai, Amporn (My University, 2014)
This article presents a novel magnetotransistor based on carrier recombination-deflection effect for detecting magnetic field in three dimensions (BX, BY, and BZ) by relying on the difference between base and collector currents (ICB). This device used low biasing current. It was designed and fabricated using CMOS fabrication technology. The device structure consisted of one emitter, 4 collectors and 4 bases. All four collector terminals were connected with each other. The same was true for the four base terminals. LOCOS oxide was grown to surround the emitter area to limit lateral carrier loss, and therefore reducing the overall biasing current. The experiment showed that, at 0.2 mA of biasing current, the B X, BY and B-Z direction sensitivity to magnetic field within the range of 0-400 mT are 2, 5 and 14.5%/T, respectively. This research on the merged magnetotransistor produced magnetic sensors with small size, high performance with wide range of applications. © 2014 Elsevier Ltd.
Keywords: Carrier deflection; Carrier recombination; Lorentz force; Merged magnetotransistor